PENENTUAN KUALITAS KAYU JATI SECARA VISUAL MENGGUNAKAN METODE LEARNING VECTOR QUANTIZATION - Ignatius Ngesti Yuwono; Robertus Krismanto; Antonius Sugianto (Universitas Tarumanagara, 2022)
Teak Wood (Tectona Grandis) is one of the best woods of the many types of wood species used in Indonesia as material for furniture and building construction. The quality of teak is determined by many factors, one of which is the wood grain pattern density. Currently the determination of the quality of teak wood visually by looking at the wood grain pattern in teak is done by experts who are experienced in the field. Visual classification of teak based on wood grain pattern density is divided into three, namely: grade A: wood grain pattern with high density; grade B: medium density of wood grain pattern; grade C: wood grain pattern with low / no density. Artificial neural networks are information processing systems such as processing in the human brain, which have been widely used in many applications for classification. In research for the classification of teak wood density patterns using Learning Vector Quatization. From the results of testing using the LVQ teak wood density classification method obtained sufficient accuracy that is equal to 68.7% with a kappa value of 0.521, this means that there is a sufficient match between the assessment and the density of the target assessment using LVQ.Keywords: teak wood; artificial neural network; image processing; LVQAbstrakKayu Jati (Tectona Grandis) adalah salah satu jenis kayu terbaik dari banyak jenis spesies kayu yang digunakan di Indonesia sebagai bahan untuk furnitur dan konstruksi bangunan. Kualitas kayu jati ditentukan oleh banyak faktor, salah satunya adalah pola serat kayu. Saat ini penentuan kualitas kayu jati secara visual dengan melihat pola serat kayu jati dilakukan oleh para ahli yang berpengalaman di lapangan. Klasifikasi visual jati berdasarkan kepadatan pola serat kayu dibagi menjadi tiga, yaitu: kelas A: pola serat kayu dengan kualitas tinggi; kelas B: pola serat kayu kualitas sedang; grade C: pola serat kayu dengan kualitas rendah. Jaringan syaraf tiruan adalah sistem pemrosesan informasi seperti pemrosesan di otak manusia. Jaringan syaraf tiruan telah banyak digunakan dalam banyak aplikasi untuk klasifikasi. Penelitian klasifikasi pola kayu jati ini menggunakan metode Learning Vector Quatization (LVQ). Dan dari hasil pengujian menggunakan metode LVQ untuk klasifikasi pola kayu jati, diperoleh akurasi yang cukup yaitu sebesar 68,7%, ini berarti ada kecocokan yang cukup antara penilaian pola serat kayu oleh expert dengan penilaian pola serat kayu dengan menggunakan metode LVQ.